Genetic and phenotypic diversity, heritability, and correlation between the quantitative characters on 30 sweet potato germplasms in Lampung, Indonesia - RATNA DEWI; SETYO DWI UTOMO; M. KAMAL; PAUL B. TIMOTIWU; SITI NURDJANAH (Society for Indonesian Biodiversity, 2019)
Dewi R, Utomo SD, Kamal M, Timotiwu PB, Nurdjanah S. 2019. Genetic and phenotypic diversity, heritability, and correlation between the quantitative characters on 30 sweet potato germplasms in Lampung, Indonesia. Biodiversitas 20: 380-386. Local food commodities such as sweet potato is an alternative rice substitute food which has high nutritional content. Estimating the value of genetic diversity, heritability and correlation between quantitative characters with the weight of large storage root per plant, is needed in the selection program for the development of quality sweet potato varieties. The purpose of this study was to find out information about genetic diversity, heritability, and correlation between quantitative characters with the weight of large storage root in 30 local Lampung sweet potato germplasm, introduction and national superior genotypes. The study was carried out in the Politeknik Negeri Lampung experimental garden from September 2017 to January 2018. Using 30 genotypes of sweet potato germplasm. The study was arranged in a randomized block design (RBD) with two replications. The results showed that all characters (weight of large storage root, number of large storage root, storage root length, storage root diameter, vines length, segment length, vines diameter, and weight of vines) had a value of genetic diversity, whereas wide phenotypic diversity and has a high value of heritability. Genetic factors more influence all characters in this study compared to environmental factors. The results of the correlation analysis showed that the characters of the weight of large storage root, storage root length, and storage root diameter were positively correlated with the weight of the storage root. Whereas, the length of vines is negatively correlated with the weight of large storage. The character of the segment length, vines diameter and weight of vines did not correlate with the weight of large storage root. The character of the segment length, vines diameter and weight of vines did not correlate with the weight of large storage root. Cluster analysis results from 30 sweet potato genotypes were grouped into 13 clusters. Based on similarity of character and provenance. The germplasm of 30 Sweet potato genotypes found in Politeknik Negeri Lampung can be selected and crossed to create the desired superior characters.